BCM452: Construction Health and Safety / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2018)
The course develops an awareness of the paramount importance of health, safety and protection of environment in construction. It covers the understanding of development of construction health and safety policy, plans and procedures. The course includes identifying the health hazards and understanding the risk assessment and control.